Eco-Friendly Farming: The Role of Livestock Waste Processing in Organic Fertilizer Production in Lempake, Samarinda - Aprylasari, Dede; Indana, Khoiru; Wibowo, Ari; Azizah, Siti (Graduate School, Universitas Brawijaya, 2025)
Sustainable agriculture is one solution to address global challenges such as climate change and environmental degradation. A critical aspect of sustainable agriculture is managing organic waste, especially livestock waste, which is often overlooked despite its great potential as a resource. In Lempake, Samarinda, the livestock sector produces quite significant livestock waste, but the management of this waste is still limited. This study aims to optimize the processing of livestock waste into environmentally friendly organic fertilizer and explore the obstacles and solutions in processing this waste. The survey results show that livestock waste such as cow, goat, and poultry manure can be converted into quality organic fertilizer by composting and using additional materials such as straw, leaves, and decomposer microorganisms (EM4). The resulting organic fertilizer can increase soil fertility, improve soil structure, and reduce dependence on synthetic chemical fertilizers. The main obstacles are livestock farmers' lack of knowledge and skills, limited technology and infrastructure, and low environmental awareness. The proposed solutions include training for livestock farmers, provision of technology and infrastructure, and increasing environmental awareness. This research is expected to contribute to sustainable agriculture and ecological conservation and become a model for other regions. Keywords: Organic fertilizer, Livestock manure waste, Sustainable agriculture